Koala ocular disease grades are defined by chlamydial load changes and increases in Th2 immune responses - Phillips, Samuel; Madden, Danielle; Gillett, Amber; Quigley, Bonnie L.; Jelocnik, Martina; Bommana, Sankhya; O’Meally, Denis; Timms, Peter; Polkinghorne, Adam (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionThis study employs bulk RNA sequencing, PCR, and ELISA assays to analyze the pathological factors affecting the outcomes of C. pecorum ocular infections in koalas. It investigates the immune responses and gene expression profiles associated with various stages of koala ocular chlamydiosis.MethodsA cohort of 114 koalas from Queensland, Australia were assessed, with 47% displaying clinical signs of ocular disease. Animals were classified into three cohorts: acute active disease (G1), chronic active disease (G2), and chronic inactive disease (G3), along with subclinical Chlamydia pecorum positive (H2) and healthy (H1) cohorts.ResultsAnalysis of clinical, microbiological, humoral immune and cellular immune biomarkers revealed varying chlamydial loads and anti-chlamydial IgG levels across disease grades, with a negative correlation observed between ocular chlamydial load and anti-chlamydial IgG. Koala ocular mucosa gene expression analysis from 27 koalas identified shared expression pathways across disease cohorts, with a significant upregulation of IFNγ expression and tryptophan metabolism in all disease stages.DiscussionThese findings help elucidate immune response dynamics and molecular pathways underlying koala ocular chlamydiosis, providing insights crucial for disease management strategies.